ANALYSIS OF ASEAN CAPITAL MARKET PERFORMANCE IN COMPARISON TO THE INDONESIA CAPITAL MARKET ON THE INDONESIA STOCK EXCHANGE - Gusrina, Bella; Lastri, Surna; Sari, Dessy Purnama (University Muhammadiyah Aceh, 2025)
This study aims to analyze the relationship between the stock market indices of ASEAN countries namely, the Kuala Lumpur Composite Index (KLCI), Straits Times Index (STI), Stock Exchange of Thailand Index (SETI), Philippine Stock Exchange Index (PSEI), and Hanoi Stock Exchange 30 (HNX30) with the Composite Stock Price Index (IHSG) on the Indonesia Stock Exchange throughout 2023. The research utilizes weekly data from January to December 2023 and applies a multriple linear regression analysis method. The findings reveal that the Kuala Lumpur Composite Index (KLCI) has a significant positive impact on the Composite Stock Price Index (IHSG), while the Stock Exchange of Thailand Index (SETI) has a significant negative impact on the Composite Stock Price Index. Conversely, the Straits Times Index (STI), Philippine Stock Exchange Index (PSEI), and Hanoi Stock Exchange 30 (HNX30) do not exhibit a significant influence on the Composite Stock Price Index.